TINJAUAN YURIDIS TENTANG PERMOHONAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG YANG DIAJUKAN OLEH SATU KREDITUR (Studi Kasus Perkara Nomor 4/Pdt.Sus-PKPU/2020/PN Mdn) - Farhana Halifa Putri Yoza; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
A debtor can only be declared bankrupt if it has been decided by the Commercial Court. However, prior to the application for bankruptcy, the debtor and creditor may apply for a Suspension of Debt Payment Obligation (PKPU) to the Commercial Court. PKPU is an alternative debt settlement to avoid bankruptcy. Basically, the granting of PKPU to debtors is intended so that debtors who are in a state of insolvency have the opportunity to submit a reconciliation plan, either in the form of an offer to pay the debt in whole or in part for the debt. The purpose of writing this thesis: First, to find out the procedure for Postponement of Debt Payment Obligations based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. Second, to find out the judge's considerations in case Number 4/Pdt.SusPKPU/2020/PN Mdn at the Medan District Court which in its decision granted the request for Suspension of Debt Payment Obligations submitted by one creditor, it is correct if it is reviewed by Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations.The type of research used in this legal research is normative legal research. the approach used by the researcher is a normative juridical approach. Analysis of the data used is the author analyzes the data qualitatively. In drawing conclusions, the writer uses deductive thinking method, which is a way of thinking that draws conclusions from a general statement or proposition into a specific statement.From the results of the research, the first is regarding the procedure for Postponement of Debt Payment Obligations based on Law Number 37 of 2004 concerning Bankruptcy and Debt Payment Delays that in the provisions of the law there are 14 (fourteen) procedures that must be passed. It should be said that the provisions of the law governing this matter can be said to be of a maximum nature. Keywords: Postponement of Debt Payment Obligations – Debtors – Creditors